2015
DOI: 10.21273/hortsci.50.9.1387
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Deficit Irrigation and Crop Load on Leaf and Fruit Nutrition of Fertigated ‘Ambrosia’/‘M.9’ Apple

Abstract: Mature, fruiting ‘Ambrosia’/‘M.9’ apple [Malus ×sylvestris (L.) Mill. var. domestica (Borkh.) Mansf.] trees were subjected over three growing seasons to a split-plot experimental design involving four irrigation main plot treatments and three subplot crop load treatments with six replicates. This semiarid production region is traditionally irrigated 01 May to 01 Oct. during which time an average of ≈ 15 cm of precipitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Nutrient uptake and transport efficiency (NUTE) in apple are genetically complex traits specific to each nutrient and involving both root-specific (referring to the rootstock in commercial production conditions) and scion-specific components 141,142 . NUTE is influenced by a wide range of physiological and morphological mechanisms, such as interaction with soil biota, active, and passive transport, vessel composition and size, root induced hormone concentration 124,143 , and interaction with pH, as well as management options such as crop load and irrigation 144 . Classical QTL mapping revealed QTLs influencing scion leaf concentrations for thirteen minerals 145 .…”
Section: Water and Nutrient Use Efficiency Genes And Genetics: Absorbmentioning
confidence: 99%
“…Nutrient uptake and transport efficiency (NUTE) in apple are genetically complex traits specific to each nutrient and involving both root-specific (referring to the rootstock in commercial production conditions) and scion-specific components 141,142 . NUTE is influenced by a wide range of physiological and morphological mechanisms, such as interaction with soil biota, active, and passive transport, vessel composition and size, root induced hormone concentration 124,143 , and interaction with pH, as well as management options such as crop load and irrigation 144 . Classical QTL mapping revealed QTLs influencing scion leaf concentrations for thirteen minerals 145 .…”
Section: Water and Nutrient Use Efficiency Genes And Genetics: Absorbmentioning
confidence: 99%
“…Such challenges can be mitigated by selecting the appropriate rootstocks. In the last three decades, the majority of Ambrosia TM apple production and a number of horticultural studies have been based on Malling 9 rootstock [ 15 , 16 ]. In recent years, there has been a slow increase in the use of other rootstocks such as Malling 26 (M.26), Budagovsky 9 (B.9), and innovative Geneva rootstocks that possess resistance to orchard biotic stressors such as fire blight, phytophthora, and aphids [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…High crop load extends ripening (Atay et al, 2017). Leaf and fruit nutrient concentrations can be affected by crop load (Neilsen et al, 2015). Reig et al (2018) found that leaf and fruit minerals are moderate to low, correlate with cumulative crop load in 'Fuji' apple grafted on different rootstocks under New York conditions.…”
Section: Introductionmentioning
confidence: 99%